Homological bulk–edge correspondence for Weyl semimetals. (18th March 2021) - Gomi, Kiyonori
Abstract: For a certain translationally invariant tight-binding model of 3D Weyl semimetals, we establish a bulk–edge correspondence as an equality of two relative homology classes, based on an idea of Mathai and Thiang: [14 ] and [15 ] From spectral information on the edge Hamiltonian, we construct a relative homology class on the surface momentum space. This class agrees with the image under the surface projection of a homology class on the bulk momentum space relative to the Weyl points, constructed from the bulk Hamiltonian. Furthermore, the relative homology class on the surface momentum space can be represented by homology cycles whose images constitute Fermi arcs, the loci where the edge Hamiltonian admits a zero spectrum.